Australian State and Territory Eclectic Approaches to Obesity Prevention in the Early Years: Policy Mapping and Perspectives of Senior Health Officials - Esdaile, Emma K.; Gillespie, James; Baur, Louise A.; Wen, Li Ming; Rissel, Chris (Frontiers in Public Health, 2022)
Background The international increase in the prevalence of childhood obesity has hastened in recent decades. This rise has coincided with the emergence of comorbidities in childhood—such as type II diabetes, non-alcoholic fatty liver disease, metabolic syndrome, sleep apnoea and hypertension—formerly only described in adulthood. This phenomenon suggests global social and economic trends are impacting on health supportive environments. Obesity prevention is complex and necessitates both long-term and systems approaches. Such an approach considers the determinants of health and how they interrelate to one another. Investment in the early years (from conception to about 5 years of age) is a key life stage to prevent obesity and establish lifelong healthy habits relating to nutrition, physical activity, sedentary behavior and sleep. In Australia, obesity prevention efforts are spread across national and state/territory health departments. It is not known from the literature how, with limited national oversight, state and territory health departments approach obesity prevention in the early years. Methods We conducted a qualitative study including policy mapping and interviews with senior officials from each Australian state/territory health department. A series of questions were developed from the literature to guide the policy mapping, drawing on the World Health Organisation Ending Childhood Obesity Report, and adapted to the state/territory context. The policy mapping was iterative. Prior to the interviews initial policy mapping was undertaken. During the interviews, these policies were discussed, and participants were asked to supply any additional policies of relevance to obesity prevention. The semi-structured interviews explored the approaches to obesity prevention taken in each jurisdiction and the barriers and enablers faced for policy implementation. Thematic analysis was used to analyse the data, using NVivo software. Results State and territory approaches to obesity prevention are eclectic and while there are numerous similarities between jurisdictions, no two states are the same. The diversity of approaches between jurisdictions is influenced by the policy culture and unique social, geographic, and funding contexts in each jurisdiction. No Australian state/territory had policies against all the guiding questions. However, there are opportunities for sharing and collaborating within and between Australian jurisdictions to establish what works, where, and for whom, across Australia's complex policy landscape. Conclusions Even within a single country, obesity prevention policy needs to be adaptable to local contexts. Opportunities for jurisdictions within and between countries to share, learn, and adapt their experiences should be supported and sustained funding provided.